A prospective study of breed differences in the thermal pain sensitivity of dogs. (January 2018) - Bowden, James; Beausoleil, Ngaio J.; Stafford, Kevin J.; Gieseg, Michael A.; Bridges, Janis
Abstract: Objective: To compare the thermal nociceptive thresholds (TNTs) of dogs from three working/sport breeds. Study design: Experimental prospective study. Animals: Thirty healthy adult dogs of mixed age, sex and reproductive status, 10 of each of three breeds: Harrier Hound, Greyhound and New Zealand Huntaway. Methods: On one day of each week for 4 weeks, unrestrained dogs were tested six times. TNTs were measured using a remotely activated device comprising a thermode attached to the thoracic limb, controlled by a microprocessor attached to the animal. Latency to exhibit behaviour indicative of nociception after initiation of heating and the temperature of the thermode at the point of behavioural response were measured. Linear mixed-effects models were fitted to the data, with dog included as a random effect, initial thermode temperature as a covariate and day, week and breed as fixed effects. Results: Initial thermode temperature significantly affected dogs' latency to respond ( p < 0.001). Breed had a significant effect on both latency to respond and response temperature. Huntaways took longer to respond than Harriers or Greyhounds. For example, when the initial thermode temperature was 30 °C, Huntaways took 39.0 seconds to respond compared with 35.8 seconds for Harriers and 36.8 seconds for Greyhounds. Huntaways also responded at higher temperatures (mean ± standard deviation: Huntaways 49.7 ± 1.3 °C, Harriers 48.4 ± 1.6 °C and Greyhounds 48.7 ± 1.6 °C). Conclusions and clinical relevance: Huntaways appeared to be less sensitive to thermal pain than the other breeds. Such information could be used by researchers and clinicians to better understand the generalizability of data gathered from a specific breed to the wider canine population or to tailor more effective pharmacological approaches to pain management in dogs.